Development of Instagram and YouTube Content Videos' for Online Learning - Septinda Rima Dewanti; Sujarwo Sujarwo (Jurnal Penelitian Ilmu Pendidikan, 2021)
Instructional videos uploaded on Instagram and Youtube for online learning media teachers are facing a problem regarding the student's complicity in the learning process. To captivate the student's interest in the learning activity, the teacher needs to use innovative media. The study aims to develop an instructional video that is uploaded on Instagram and YouTube. The research used educational design research. The research procedure is 1) analysis of practical problems by the researcher; 2) development of prototype solutions informed by existing design principles; 3) testing and refinement. The study used questionnaires and interviews as the instrument. The number of subjects is 40 students The study results show that the video that was developed meets the criteria relevance, consistency, practicality, and effectiveness. The average score of the study is >3. The conclusion of the research is the instructional video uploaded on social media can improve students' activities in online learning. Recommendation for future study is to pay more attention to the urgency of instructional media in online education. Pengembangan Konten Video pada Instagram dan YouTube untuk Pembelajaran Daring Salah satu kendala pelaksanaan pembelajaran secara online adalah rendahnya keterlibatan mahasiswa. Pembelajaran dengan memanfaatkan media sosial diharapkan dapat meningkatkan minat belajar mahasiswa. Tujuan dari penelitian ini adalah untuk mengembangkan video pembelajaran yang dapat diunggah di media sosial Instagram dan YouTube. Metode penelitian yang digunakan pada penelitian ini adalah educational design research. Prosedur penelitian yang dilakukan meliputi 1) penelitian pendahuluan; 2) tahap pengembangan atau prototipe; 3) tahap asesmen/evaluasi. Instrumen penelitian yang digunakan adalah kuisioner dan pedoman wawancara. Jumlah subjek pada penelitian ini adalah 40 mahasiswa. Hasil dari penelitian ini adalah video pembelajaran yang dikembangkan memenuhi kriteria relevansi, konsistensi, kegunaan dan keefektifan yang ditunjukkan dengan rata-rata skor penilaian produk >3. Kesimpulan dari penelitian ini adalah media berupa video yang diunggah di media sosial, efektif membantu pelaksanaan pembelajaran daring bagi mahasiswa. Penelitian ini memberikan rekomendasi kepada peneliti selanjutnya terhadap urgensi penggunaan media pembelajaran yang menarik minat mahasiswa sehingga penelitian yang lebih mendalam tentang media pembelajaran perlu dilakukan.